The literary 100 a ranking of the most influential novelists, playwrights, and poets of all time - Burt, Daniel S. (Facts on File library of world literature., 2009)
Here is the revised and expanded edition of Daniel S. Burt's assessment of the 100 most influential novelists, playwrights, and poets of all times and cultures--now with 25 additional entries and some reassessments as well as 25 new black-and-white photographs and illustrations. All of the writers selected have helped to redefine literature, establishing a standard with which succeeding generations of writers and readers have had to contend. The ranking attempts to discern, from the broadest possible perspective, what makes a literary artist great and how that greatness can be measured and compared. Each profile distills the essence of the writer's career and character to help prompt consideration of literary merit and relationships by the reader.